Tetracycline Resistance Gene Profiles in Red Seabream (Pagrus major) Intestine and Rearing Water After Oxytetracycline Administration - Obayashi, Yumiko; Kadoya, Aya; Kataoka, Naoto; Kanda, Kazuki; Bak, Su-Min; Iwata, Hisato; Suzuki, Satoru (Frontiers in Microbiology, 2020)
Marine aquaculture fish and the environment are possible hot spots for the maintenance and spread of antibiotic resistance genes (ARGs). We here show the time courses of changes of six tetracycline resistance genes (tet) in fish rearing seawater and fish intestine in tank experiments. Experimental tanks were prepared as oxytetracycline (OTC) administration tanks and those without OTC. It was found that tet(B), tet(M) and tet(W) were dominant in seawater among the six tet genes. tet(B) and tet(M) abundances increased immediately after OTC administration, indicating that OTC served as a selective pressure to increase the proportion of tet-possessing bacteria. In contrast, the abundance of tet genes in the fish intestine did not differ between the with- and without-OTC administration groups, and clearly was not altered by OTC administration. Profile changing of tet in seawater and fish intestine did not synchronize. These observations suggested that the dynamics of intestinal tet-possessing bacteria do not directly reflect the environment, but reflect selection within the intestine.